Do the various leisure forms have equal effects on mental health? A longitudinal analysis of self-selected leisure activities - Junyi Bian; Junyi Bian; Zubing Xiang (Frontiers Media S.A., 2023)
The deteriorating trends of unbalanced income, progressive age-related health problems, and loss of traditional ties necessitate ever-flexible interventions that are helpful to overcome a decline in Chinese adults' mental health. This study aimed to test whether engagement in different domains of leisure is associated with a composite index of mental health, both concurrently and subsequently. Longitudinal data including 10,968 participants (females = 5,804) with a mean age of 46.01 years in the Chinese General Social Survey (CGSS) were analyzed using generalized estimating equations with a logit link. The results showed that face-to-face experiences, such as sports with all ORs of < 1 at the significance level of α = 0.01 and meeting with all ORs of < 1 at the significance level of α = 0.01 except daily in-person meeting frequency, are important for protecting mental health owing to the increasing social support by building close ties. The results also indicate that online leisure with all ORs < 1 at the significance level of α = 0.01 has positive effects on lowering the odds of depression. In addition, receptive cognitive leisure, such as watching television or movies with all ORs < 1 at the significance level of α = 0.05 level, was not consistently associated with depression. However, active cognitive leisure, such as reading with all ORs of < 1 at a significance level of α = 0.01, was associated with lower odds of depression.